Power/Knowledge in the Governance of Natural Resources: A Case Study of Medicinal Plant Conservation in the Eastern Cape - Soul Shava (Environmental Association of Southern Africa, 2011)
This article explores the power/knowledge relations at the knowledge generating interface between a modern community development organisation and a traditional health practitioner community in a town in the Eastern Cape, South Africa, through the lens of Foucaldian governmentality. This case study is part of a broader study which explores power/knowledge relationships in the representation and application of indigenous knowledges in selected environmental education and community development contexts. This study traces the various loci of power/knowledge and their implications in a project focusing on the conservation of traditional medicinal plants in which the community development organisation and traditional health practitioner community were involved as key partners. The case study provides a micro-setting to analyse natural resource governance, which reveals how power located in modern institutions is reinforced by the generation and accumulation of disciplinary (scientific) knowledge as a hegemonic regime of truth that is applied in the governance of medicinal resources. It also reveals the location of power within the traditional healer community on the other hand and how this is maintained by the resilient cultural retention of medicinal knowledge and related practices within the community against a background of dominant Western medical practice.